Enhanced transition-temperature reduction in a half-sphere Au/VO2 core-shell structure : local plasmonics versus induced stress and percolation effects - Wang, Shancheng (2019)
VO2 undergoes metal-insulator transition (MIT) at the transition temperature (τc) of 68 °C, accompanied by a sharp optical response change. A unique Au/VO2 half-sphere core-shell structure is fabricated to study the temperature-dependent plasmonic effects and the thermochromic response for smart window applications. By increasing the Au core size, the surface plasmonic resonance wavelength of the VO2 high-temperature rutile phase is tuned from 600 to 720 nm and confirmed by simulations. Meanwhile, τc of VO2 is reduced by up to 10 °C, which is thought to be associated with plasmon-induced or percolation-enhancement-related effects. Modification of τc occurs on the optical domain only and not in the electrical domain. The in-depth analysis suggests that the interaction of the plasmon between Au and VO2 in the near field triggers different mechanisms, which reduce the τc of VO2, in particular under high irradiation levels. However, under normal irradiation levels the main contributing effect is found to be thermal strain at the nanoparticles‘ surface.